MY SAY: Treat maids with respect and dignity - Abd Razak, Dzulkifli (2009)
Ask any 18yearold Malaysian girl from a middleincome urban family background if she would be willing to clean, wash and cook daily for a family for less than RM800 per month, and chances are she will say: "No thanks". Not even if she were offered the "privileges" that she enjoys at home — her own room, phone and Internet access, unlimited food supply, and time off with her friends. But if fulltime foreign maids are willing to do the job without the comforts of a privileged environment, why pay them less than RM800? Is it because they come from a remote village in a foreign country?